ANALYZING THE INFLUENCE OF INTERNAL CONTROL SYSTEM AGAINTS ETHICAL BEHAVIOR OF EMPLOYEE (Case Study on PT. Japfa Comfeed, Tbk) - Riswan Pramono; Unti Ludigdo (Jurnal Ilmiah Mahasiswa FEB, 2012)
Keywords: Internal Control, Ethical behavior, employee behavior, company behavior The Purpose of this study is to analyze and explain the effect of Internal control system in company on the effect of the employee ethical behavior. The researcher is motivated to do a study on the company internal control system is because the control of the company internal control are really effected on the employee behavior because the internal control are as the control of the company in doing proper ethics in the workplace or vise versa if the internal control are bad also will makes the employee easier to do unethical thing. The samples of this research are PT. Japfa Comfeed Indonesia. Tbk. Writer analyze how the internal control of this company well implement by the employee and how the ethical of the employee doing their works. This research is explanatory research, which is research that explains the causal relationships between variables through hypothesis testing and simple linear regression analysis to measure the effect of Internal Control on ethical behaviors. Simple regression analysis is used to determine whether Internal control which is the independent variable are able to measure the Ethical behavior as the dependent variable. Based on Simple linear regression analysis, simultaneously, all independent variables significantly affect Ethical Behavior. But partially, because of the big areas of ethical behavior internal control only affecting not all of the employee ethics. There are probably some other variables that can effecting ethical behavior.